NEXT-GENERATION ENTERPRISE SECURITY THROUGH ZERO-TRUST, PRIVACY AND BLOCKCHAIN TECHNOLOGIES - Siva Prakash Bikka, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Modern enterprise environments require advanced security frameworks to address evolving threats and compliance requirements. The article examines Zero-Trust Security, Data Privacy and Compliance, and Blockchain technology implementations across healthcare, financial services, and public sector applications. By investigating the integration of artificial intelligence, cloud computing, and cybersecurity measures, the study demonstrates the effectiveness of contemporary security approaches in protecting critical assets while maintaining operational efficiency. The article provides detailed insights into successful implementation frameworks, resource allocation strategies, and performance metrics across different security domains, offering practical guidance for organizations pursuing enhanced security postures.